2013
DOI: 10.1016/j.juro.2013.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Infants Undergoing Robot-Assisted Laparoscopic Pyeloplasty Compared to Open Repair

Abstract: In our preliminary experience robotic pyeloplasty in infants is feasible and safe. The immediate outcomes are similar to those of an open approach. The robotic technique in infants currently has the benefits of improved esthetic appearance, improved pain control and similar direct costs compared to the traditional open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 17 publications
1
60
1
1
Order By: Relevance
“…[22] Dangle et al reported that the success rate of RALP was comparable to OP, even in infants. [23] In terms of limitations, our present study involved a retrospective cohort. In addition, due to the order of introduction of surgical technique from OP to LEXP, and then to RALP, patients in each surgical group reflected a chronological order so that the surgeon's experience might have played a role in the outcome of the surgery which could not be compensated for by the statistical method we used.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Dangle et al reported that the success rate of RALP was comparable to OP, even in infants. [23] In terms of limitations, our present study involved a retrospective cohort. In addition, due to the order of introduction of surgical technique from OP to LEXP, and then to RALP, patients in each surgical group reflected a chronological order so that the surgeon's experience might have played a role in the outcome of the surgery which could not be compensated for by the statistical method we used.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described by our group, the use of 8-mm ports rather than the standard 5-mm ports is preferred to allow for greater functional operating space. 12 The da Vinci robotic system is then docked on the patient's ipsilateral side.…”
Section: Techniquementioning
confidence: 99%
“…Because MIS in children has been proven safe and effective, a broad panel of procedures has been established, including relatively simple procedures (impalpable testes, varicocoele, peritoneal dialysis access, and nephrectomy for a nonfunctional kidney) and more difficult procedures such as partial nephrectomy in duplex systems, pyeloplasty, adrenal lesions, and bladder reconstructive surgery [33][34][35][36][37][38].…”
Section: Surgical Challenges In Childrenmentioning
confidence: 99%
“…The feasibility of the laparoscopic approach and its safety and efficacy have been demonstrated [25,31,33,49,50]; however, the steep learning curve of laparoscopy, the technical difficulties related to two-dimensional vision, the compromised dexterity due to the well-known fulcrum effect, and the transmission and amplification of the surgeon's hand tremor have contributed to make laparoscopy a technique that takes considerable time to master. The robot-assisted technique has the potential to allow for wider adoption of MIS in paediatric urology.…”
Section: Robotic Assisted Surgerymentioning
confidence: 99%
See 1 more Smart Citation